Game of stratagems: archetypal nature of success strategies building - Garnyk, Liudmyla Petrivna; Posokhov, Igor Mikhailovich; Snihurova, Irina Ivanivna; Sheianova, Elina Dmytrivna (Посвіт, 2019)
The purpose of the research is to analyze contemporary versions of Chinese Stratagems texts and identify «instant character» of their elements that have semantically close interpretations in different cultures and civilizations, distanced from each other mentally, geographically and chronologically, that helps us to identify their archetypal nature. The research methodology is based on approaches, borrowed from James George Frazer’s works on social anthropology and Gilbert Durand’s instrument «Imaginer» that were joined within canvas of our research methodology with traditional methods of content and event comparative analysis. The scientific novelty of our article consists in an attempt to apply archetypal meta-theory and its instruments for creating concept of intellectual card game «Stratagems» that has passed probation during 2017 – 2019 in frameworks of seminars on economics, theory of international economic relations, management, psychology and applied linguistics in National Technical University «Kharkiv Polytechnic Institute». Conclusions. During all periods of human history, numerous issues close related with strategies of sustainable development on local, regional and global levels traditionally were dependent on evolution of spiritual-philosophic domain of mankind being. Contemporary wisdom (global intellectual capital) as balanced set of tactics (theory) and based on them behavioral patterns (praxis) we have defined as interpreted and reshaped eternal knowledge by different civilizations and cultures into variety of sources and forms like games, epic stories, sacral doctrines, legends, fables and folklore. The most interesting and controversial by nature among them are group of works on Chinese Stratagems and their application for different spheres of communication and socioeconomic interactions (policymaking, consumer’s behavior, diplomacy, constructing of quality management systems, administrative management and etc.). Today globalization, as socio-economic and geopolitical process, has faced all contemporary communities with dilemma of making right choice and appropriate strategy in frameworks of interpersonal or intercultural communication (business, bilateral talks, mediation of conflicts and etc.) and also in sphere of administrative management, international economic relations and quality assurance of decision-making process. Thus, our attention focused on mentioned above issues, has being attracted by works devoted to strategic decision-making, crisis management and philosophy of quality management.

Мета дослідження – проаналізувати сучасні версії текстів Китайських Стратагем та вивчити «універсальний характер» їх елементів, що мають семантично наближені інтерпретації у різних культурах та цивілізаціях, розділених між собою ментально, географічно й у часі, що допоможе нам виявити їх архетипну природу. Методологія дослідження базується на підходах, запозичених у роботах з соціальної антропології Джеймса Джорджа Фрейзера та інструмент «Імаджинер» Жильбера Дюрана, які були поєднані у канві методології нашого дослідження з традиційними методами порівняльного аналізу змісту та подій. Наукова новизна нашої статті міститься у спробі залучити архетипну метатеорію та її інструменти для створення концепції інтелектуальної гри «Стратагеми», яка пройшла апробацію протягом 2017 – 2019 років у рамках семінарів з економіки, теорії міжнародних економічних відносин, менеджменту, психології та прикладної лінгвістики у Національному технічному університеті «Харківський політехнічний інститут». Висновки. Протягом усіх періодів історії людства численні питання, тісно пов’язані з стратегіями сталого розвитку на локальному, регіональному та глобальному рівнях, традиційно знаходилися в залежності від еволюції духовно-філософського простору людського буття. Сучасна мудрість (глобальний інтелектуальний капітал) як збалансований набір тактик (теорія) та похідних від них поведінкових патернів (практика), нами визначено як першознання, інтепретоване та видозмінене багатьма цивілізаціями і культурами у різноманітні джерела й форми, такі як: ігри, епічні історії, сакральні доктрини, легенди, байки та фольклор. Найбільш цікавими і суперечливими за своєю природою серед них є група робіт з Китайських Стратагем та їх застосування у різних сферах спілкування й соціоекономічних взаємодій (політика, психологія споживача, дипломатія, створення систем менеджменту якості, адміністра-тивний менеджмент тощо). Нині глобалізація як соціально-економічний та геополітичний процес поставила сучасні спільноти перед дилемою вибору правильної стратегії у рамках міжособистісної чи міжкультурної комунікації (бізнес, перемовини, розв’язання конфліктів тощо), а також у галузі адміністративного менеджменту та забезпечення якості процесу прийняття рішень. Тому наша увага, зосереджена на згаданих вище питаннях, була привернута до робіт, присвячених прийняттю стратегічних рішень, кризовому менеджменту та філософії менеджменту якості.
Гра Стратагем: архетипна природа побудови стратегій успіху
Keywords: stratagems; archetypes; quality management; anthropological trajectory; intellectual game; international economic relations; administrative decision-making; стратагеми; архетипи; менеджмент якості; прийняття управлінських рішень; антропологічна траєкторія; інтелектуальна гра; міжнародні економічні відносини